ANALYSIS OF THE QUALITY OF SUMMATIVE ARABIC TEST ITEMS FOR GRADE V AT AT-TAQWA ISLAMIC ELEMENTARY SCHOOL BASED ON HALADYNA’S THEORY - Rani Asyiami; Asep Sopian; Hikmah Maulani (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The quality of test items plays an important role in ensuring the validity of learning assessments, particularly in language learning, which heavily depends on wording clarity and item construction. Previous research, however, has mostly relied on quantitative analyses and has only partially examined the quality of item wording and construction through qualitative approaches, particularly in Arabic-language assessments at the elementary school level. This study aims to analyse the quality of test items in the Arabic summative assessment of Grade V at SD IT At-Taqwa by using Haladyna’s item-writing guidelines. The research was qualitative in nature and employed directed content analysis. Comprised all multiple-choice items from the 2025 summative assessment, gathered through document analysis, and analysed using Miles and Huberman's interactive model. The results show that the test items are generally of good quality, particularly in language clarity, content relevance, and structural consistency. Some weaknesses were identified, however, such as a lack of contextual variation, repetitive item patterns, and distractors that are less effective than they could be. Additionally, some items still focus on lower-level thinking skills and do not sufficiently assess language proficiency. These findings underscore the need to improve the measurement of language ability, the quality of distractors, and contextual variation in a more holistic way